Informatização na educação em saúde: avaliação de site educacional - Souza, Érika Guimarães Leal de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Health education presently experiences the incorporation of information technology, thus making access to information more practical and attainable. The initiatives to make health care scientific content available virtually have shown to be useful for teaching, health care professionals and the general population. A website, however, must be constantly managed. To promote the dissemination of the website at www.educacaoemsaude.fmb.unesp.br among faculty members and undergraduate nursing students and students at Escola Técnica de Enfermagem (Vocational Nursing School) - ETE, by evaluating, among them, its graphic and functional aspects and seeking suggestions for its improvement. This is a descriptive quantitative study for which the participants were asked to fill out an instrument designed for the study. The evaluation was performed among nursing faculty members and students at Univ Estadual Paulista Júlio Mesquita Filho – UNESP and students at Escola Técnica de Enfermagem (Vocational Nursing School) – ETEC in the city of Botucatu. The number of participants totaled 88 individuals, of whom 23 were undergraduate students, 62 were students at ETEC, and 3 were faculty members. Eighty-one were females, and 7 were males. The participants’ age ranged from 17 to 56 years. Among the items that evaluated the website, the answers prevailed from “very good” to “good”. When the participants were asked what they had thought about the website, the answers were mostly positive, and the most frequently description given was “interesting”. Among the facilities, the most frequently reported was “easily understood content”, and as regards difficulties, handling the website was the most often mentioned. One hundred percent of the answers considered the maintenance of the website to be important. Suggestions for its improvement were given, and the most frequent... (Complete abstract click electronic access below)

A educação em saúde vive hoje a incorporação de tecnologias de informação, tornando o acesso à informação mais prático e acessível. As iniciativas de disponibilizar virtualmente conteúdo científico sobre o tema saúde, têm se mostrado útil tanto para o ensino, quanto para profissionais de saúde e população em geral. Um website, porém, deve estar em constante gestão, como sua manutenção. Promover a divulgação do site www.educacaoemsaude.fmb.unesp.br entre os docentes e discentes de graduação enfermagem e alunos da Escola Técnica de Enfermagem - ETEC, avaliando entre eles seus aspectos gráficos e funcionais e buscando sugestões para seu aprimoramento. Trata-se de um estudo quantitativo descritivo para a qual foi solicitado aos participantes o preenchimento de um instrumento elaborado para a pesquisa. A avaliação foi realizada entre docentes e discentes de enfermagem da Universidade Estadual Paulista Júlio Mesquita Filho – UNESP e alunos da Escola Técnica de Enfermagem – ETEC, do município de Botucatu. O número de participantes totalizou 88 pessoas, sendo 23 discentes, 62 alunos da ETEC e 3 docentes, sendo 81 do sexo feminino e 7 do sexo masculino. A faixa etária se apresentou entre 17 e 56 anos. Entre os itens que avaliavam o site, as respostas prevaleceram entre “muito bom” e “bom”. Quando questionado aos participantes o que achou do site, as respostas foram em grande parte positivas, sendo a mais citada como “interessante”. Entre as facilidades a mais citada foi conteúdo de fácil entendimento e entre as dificuldades o manuseio do site. 100% das respostas consideraram importante a manutenção do site. Foram relatadas sugestões para aprimoramento do site, entre as mais citadas à manutenção e atualização constante do site disponibilizando mais informações. O web site foi avaliado de forma satisfatória pela maioria dos participantes... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Enfermagem em Saúde; Educação sanitária; Avaliação educacional; Tecnologia educacional